SWOT Reveals Detailed Dynamics of Longitudinal River Slope in the Missouri River Basin - Liguang Jiang; Karina Nielsen; Ole B. Andersen; Junguo Liu (Geophysical Research Letters)
Abstract River water surface slope (WSS) is a crucial variable for a wide range of studies in hydrology, hydraulics, and morphology. However, current in situ and remote sensing methods have limitations in characterizing the WSS of global river systems. Here, we present an exploration of SWOT satellite data for studying WSS and longitudinal profiles in the Missouri River basin. Using 1‐day repeat data over 3 months, our results show that SWOT not only captured temporal variations in reach‐scale WSS, but also resolved sub‐reach local variations in WSS, revealing the intricate non‐uniform and unsteady nature of river flows. Such finer local WSS revealed slow flood wave propagation in the James River due to its low gradient. Moreover, the longitudinal profiles from SWOT revealed significant backwater effects at the confluence of the Missouri and Yellowstone rivers. This study offers new insights into river WSS dynamics, suggesting the great potential of SWOT for river science.